Proximity and Preference : Problems in the Multidimensional Analysis of Large Data Sets - Golledge, Reginald G. (Book collections on Project MUSE., 1982)
How does one design experiments for collecting large volumes of data such as those needed for marketing surveys, studies of travel patterns, and public opinion polls? This is a common problem for social and behavioral scientists. The papers in this collection address the problems of working with large data sets primarily from the perspectives of geography and psychology, two fields that share a common quantitative research methodology. After an introductory paper on substantive and methodological aspects of the interface between geography and psychology, the book is divided into three sections.